Study of the Prevalence of dermatophyte in Wasit Governorate and Evaluation of the Efficacy of Extracts of Garlic (Allium sativum) - Zahraa Khalid Ali; Azhar Jabbar Khalaf Al-Subaihawi; Tamarah qaysalmohammediand; Ali kareem Sarbout (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study assessed the prevalence of dermatophyte infections among patients at Al-Karama Teaching Hospital in Wasit Governorate, Iraq. A total of 100 samples were collected, with 88 positive for dermatophytes, yielding an 88% positivity rate. The predominant genera identified were Trichophyton (64.77%), Microsporium (23.86%), and Epidermophyton (11.36%), with Trichophyton rubrum being the most common species (39.77%). The most affected sites were Tinea manum (28.6%), Tinea pedis (22.9%), and Tinea facies (17.1%). Infection rates were higher in females (56.8%) and peaked in the 21-30 age group (51.4%). The antifungal activity of aqueous and alcoholic garlic extracts was evaluated, showing the alcoholic extract's inhibition rate against T. rubrum (35.96 mm) to be comparable to Clotrimazole (46.94 mm). High-Performance Liquid Chromatography (HPLC) identified eight phenolic compounds in the extracts, indicating garlic's potential therapeutic properties.